2020
DOI: 10.26719/2020.26.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Language barriers to studying medicine in English: perceptions of final-year medical students at the Arabian Gulf University

Abstract: Background: English is the language of instructions in many medical schools in the Arab world. Its use may create a language barrier and adversely affect an individual's learning and later professional life. Aims: This study examined the views of final-year Arab medical students of a language barrier and its effect on their learning and academic performance, and their language preference for medial education. Methods: All final-year medical students (n = 142, 62% females) at the Arabian Gulf University, Bahrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…9 Moreover, an Arabic study conducted among final year medical students reports that 72% of the students felt confident in taking medical history in Arabic and 66% felt easier to communicate with the patients in Arabic. 10 However, another study, shows that students were less confident in taking patient history in their local language than in English. 5 In another Arabic study, 72.2% of students said they felt confident in taking a medical history in English, while 27.8% of students expressed confidence in taking medical history in Arabic 11 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, an Arabic study conducted among final year medical students reports that 72% of the students felt confident in taking medical history in Arabic and 66% felt easier to communicate with the patients in Arabic. 10 However, another study, shows that students were less confident in taking patient history in their local language than in English. 5 In another Arabic study, 72.2% of students said they felt confident in taking a medical history in English, while 27.8% of students expressed confidence in taking medical history in Arabic 11 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Moreover, a Bahraini study explored language barriers in final year medical students found that only two-thirds of students were confident in communicating with patients in Arabic, evidently noting that this issue is still detectable in senior medical students. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] In Bahrain, another study further showed that even though students reported that learning medicine in a second language did not alter their academic performance, over one-third of students thought that combining English and Arabic in their medical curriculum could be of benefit, which according to the author indicates that students believed and held into the importance of Arabic language in medical education. [ 16 ] Furthermore, a Saudi study also showed that medical students found that Arabic-English code-switching in the classroom was, in fact, more desirable for course content comprehensibility. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…Matthews and Van Wyk ( 17 ) observed an enhancement in communicative competence in students, but they also identified an ongoing need for additional linguistic support. Tayem et al ( 57 ) reported varied responses related to the perceived language barrier in medical studies; while many students did not view language as an obstacle, there was a clear distinction between those proficient in English and those who were not. Interestingly, a significant majority of students were unsure of medical terms in Arabic, yet confident in their ability to communicate with patients in Arabic, revealing a dichotomy in language use and preference.…”
Section: Main Findingsmentioning
confidence: 99%